Neural Progenitor Cell Terminology - Martínez-Cerdeño, Verónica; Noctor, Stephen C. (Frontiers in Neuroanatomy, 2018)
Since descriptions of neural precursor cells (NPCs) were published in the late 19th century, neuroanatomists have used a variety of terms to describe these cells, each term reflecting contemporary understanding of cellular characteristics and function. As the field gained knowledge through a combination of technical advance and individual insight, the terminology describing NPCs changed to incorporate new information. While there is a trend toward consensus and streamlining of terminology over time, to this day scientists use different terms for NPCs that reflect their field and perspective, i.e.; terms arising from molecular, cellular, or anatomical sciences. Here we review past and current terminology used to refer to neural precursor cells, including embryonic and adult precursor cells of the cerebral cortex and hippocampus.